Reduction of Spectral Radiance Reflectance During the Annular Solar Eclipse of 21 June 2020 Observed by EPIC - Wen, Guoyong; Marshak, Alexander; Herman, Jay; Wu, Dong (Frontiers in Remote Sensing, 2022)
The annular solar eclipse on June 21, 2020 passed across desert areas (parts of Central and Eastern Africa, the southern Arabian Peninsula), partly cloudy regions (parts of South Asia and the Himalayas), and mostly cloudy region in East Asia. Moving around the Earth-Sun Lagrange 1 point (L1), the EPIC (Earth Polychromatic Imaging Camera) instrument on the DSCOVR (Deep Space Climate Observatory) spacecraft captured three sets of images of the sunlit Earth during the eclipse, allowing us to study the impact of solar eclipse on reflected solar radiation when the underlying surface and/or cloudy conditions in the Moon’s shadow are quite different. We found that (1) EPIC observed global average spectral as well as spectrally averaged reflectance reductions during the annular solar eclipse are quite different from those during the total solar eclipse of 21 August 2017; (2) the reduction of spectral reflectance depends strongly on underlying surface properties and cloud fraction.